Pupil dilation with intracameral lidocaine during phacoemulsification: Benefits for the patient and surgeon - Nikeghbali Aminollah (Indian Journal of Ophthalmology, 2008)
Topical and/or intracameral administration of anticholinergic and/or sympathomimetic mydriatic agents which are usually used for pupillary dilation during cataract surgery, have some disadvantages such as slow onset of dilation and adverse ocular and systemic effects. We evaluated intracameral injection of preservative-free 1% lidocaine without using any preoperative or intraoperative mydriatics to induce pupil dilation in 31 consecutive eyes scheduled for phacoemulsification cataract extraction and intraocular lens implantation. Pupil diameter was measured before and 90 sec after intracameral lidocaine injection. After intracameral lidocaine injection, the mean pupil diameter was significantly greater than the baseline measurement (P< 0.001). No additional mydriatics were needed up to the end of the operations. Intracameral preservative-free lidocaine 1% has a rapid and effective mydriasis that could be a safe alternative to topical and intracameral mydriatics in phacoemulsification.